BACTERIAL VAGINOSIS: STATE OF EXPLORATION OF THE PROBLEM - I. O. Makarov; M. A. Gomberg; E. L. Borovkova; L. A. Arakelyan; E. S. Berezovskaya (IRBIS LLC, 2016)
In the literature review presents the status of the study of the problem of bacterial vaginosis during and outside of pregnancy, provides criteria of diagnostics and differential diagnostics, standards of treatment and prevention opportunities.